Efficacy of Hyaluronic Acid for Reduction Post-surgical Adhesions Following Experimental Ventral Hernial Repair in Dogs - Abdullah Alhayani, Wissam; Sami Jarad, Ahmed; A. Alkhilani, Majid; Hamid Farhan, Waleed; hatem ALjumaily, Khalid (International Journal of Psychosocial Rehabilitation, 2020)
The point of this research was to assess the productivity of hyaluronic acid (HA) for reducing postsurgical adhesions following observational ventral hernial recovery in dogs. Twelve stable adult dogs were split at random into two equal groups (n=6). In group A (control), a 3x3 cm abdominal defect was made in the dog's midline abdominal layer and polypropylene mesh reconstruction (PP) only, while in group B, a 3x3 cm abdominal defect was made in the midline abdominal wall of dogs and reconstruction with PP mesh coated with HA. Clinical outcomes on the basis of post-surgical complications, including adhesion formation, pain evaluation, and mesh shrinkage after 8 weeks of mesh hernioplasty. The result showed the efficiency of HA for reducing adhesion formation with less pain and mesh shrinkage. In conclusion, the PP mesh coated with HA is acceptable and reliable for ventral repair in dogs with less post-surgical adhesion.